Performing the operations R2→ R2 – 2R1 and R3→ R3 – 3R3, we get
Expanding along C1, we get
= 1 [3p – 2 – 3(-1 + p)]
= -2 + 3p + 3 – 3p
= 1 = RHS
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation